Development of Edugame (Quartet Cards) Regarding Snacks for School Children (PJAS) At State Elementary School in Perhentian Raja Sub-District Kampar District - Mustika Hana Harahap; Dida Akhmad Gurnida; Alamsyah Aziz (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop learning media thorugh a game referred to as edugame, in this case is using quartet cards regarding snacks for school children. This was a development research (R&D) which referred to the ADDIE development model including 4 stages, namely: Analysis to analyze module development needs, Design of the product in the form of module, Development of the module which was further assessed for feasibility by material and media expert for improvement, Implementation of the module as learning and teaching material, and Evaluation as the result which indicated that edugame (quartet cards) was feasible to use. In fact, this study only reached the development process due to time and manpower limitations. The edugame development procedures included the stages of needs analysis, literature study, media selection, preparation of teaching materials, media design, product validation, and final product improvement. The study instruments used in this study were material validation questionnaire, media validation questionnaire and parental acceptance response questionnaire. It was found that according to material experts, the edugame (quartet cards) regarding healthy snacks for students (PJAS) was included in the “very good” category, both in the aspect of material quality and the aspect of material benefit. Furtehrmore, according to media expert, such edugane was included in the “good” category in terms of media quality, language use and media layout aspects. In addition, the acceptance response variable was included in the “Very good” category in terms of ease of use, attractiveness, and efficiency aspects. Thus, based on the results of the assessment results, it can be concluded that the edugame (quartet cards) regarding healthy snacks for students was feasible to use.